Hybrid Multi-perspective NLOS Localization Framework (HM-NLOS-LF) for effective node localization in VANETs - Amuthan, A; Kaviarasan, R (International Journal of Computer Sciences and Engineering, 2019)
In Vehicular Adhoc Networks the position information of vehicles has to be exchanged between the communicating vehicles as it plays a huge responsibility in avoiding fatal accidents. Many applications rely upon the safety message which also requires location information. The vehicles within the communication range exchanges these messages. In real time scenario the direct communication between the vehicles can be blocked by the presence of road side or dynamic obstacles creating a Non Line Of Sight between the vehicles. A HYBRID MULTI-PERSPECTIVE NLOS LOCALIZATION FRAMEWORK (HM-NLOS-LF) is proposed which uses the merits of Range based, Range Free and Range optimized to identify the NLOS based on the NLOS Factor. If the NLOS Factor between 0.3 and 0.5 Range based optimization is initiated. In contrary, the NLOS Node Localization Module enforces the range-free and range-optimizations-based NLOS node detection when the NLOS determination Factor between 0.5 and 0.8 respectively.